Raw Ground Penetrating Radar Data, Wolverine Glacier, Alaska; 2013 - Salvatore G. Candela; Daniel McGrath; Christopher J. McNeil; Shad O'Neel; Louis Sass; Gabriel J. Wolken; Michael G. Loso (USGS Science Data Catalog, 2015)
Common-offset GPR surveys were conducted with a Sensors and Software 500-MHz Pulse Ekko Pro system. We collected data from the ground, towed behind a researcher on skis or snowmobile, and from the air, strapped underneath a helicopter. All of the profiles are linked to coincident GPS observations. Coincident in-situ data is provided for calibration, and may be composed of any of the following: snow pits and/or snow-pit/snow-core combinations, probe profiles, and ablation stakes. This supplemental information may be used to calibrate velocity for conversion from time domain to depth domain. This supplemental information is provided as is, with additional information specific to usage included within the in-situ folder.